Two-stage endoscopic mucosal resection is a safe and effective salvage therapy after a failed single-session approach - Tate, David J.; Desomer, Lobke; Hourigan, Luke F.; Moss, Alan; Singh, Rajvinder; Bourke, Michael J. (Endoscopy, 2017)
Background and study aims Endoscopic mucosal resection (EMR) of laterally spreading colonic lesions ≥ 20 mm (LSLs) is ideally performed in a single session (ssEMR) and avoids surgery in > 90 % of patients. We investigated whether a second attempt is safe or useful when ssEMR fails at a tertiary center.Patients and methods In a multicenter prospective observational study of patients with LSL treated by EMR at four tertiary centers over 8 years, incompletely resected LSLs were referred for surgery or underwent two-stage EMR (tsEMR). At tsEMR, the scar was located and all visible residual tissue removed by snare, with thermal treatment permitted thereafter. Scheduled surveillance was performed at 5 months (SC1) and 18 months (SC2). The primary outcome was avoidance of surgery.Results A total of 1944 LSLs (median size 35 mm) underwent EMR. ssEMR was unsuccessful in 127 lesions, 43 of which underwent tsEMR, with success in 36 (83.7 %). Compared with ssEMR, tsEMR lesions were larger (median size 50 mm vs. 30 mm; P < 0.001), exhibited more submucosal fibrosis (P < 0.001), and histology was more often tubular adenoma and less often serrated (P = 0.005). Lesions mainly required tsEMR for nonlifting (41.9 %) or poor endoscopic access (37.2 %). Failure of tsEMR was predicted by larger LSL (P = 0.03). Safety was comparable to ssEMR. Of the 33 LSLs that underwent tsEMR for benign disease and completed first surveillance, 27 (81.8 %) avoided surgery to long term follow-up.Conclusions tsEMR shows promise as a salvage therapy for LSLs that cannot be resected in a single session for patients in whom other options such as surgery are not preferred or not possible.Trial registered at ClinicalTrials.gov (NCT01368289).